THE IMPACT OF GREEN ECONOMY STANDARDS ON COMPETITIVE ADVANTAGE: THE STUDY OF ROMANIA - Hassiba Hadouga (Acta Economica, 2023)
The study aimed to reveal the impact of green economy practices in achieving competitive advantage in companies operating in Romania, according to the size of the companies. The study used the descriptive causal approach. As for the study population, it consisted of all employees in Romanian companies in the departments of quality assurance, quality control, research and development, and production. The questionnaire was used as a main tool for collecting data and information that was analyzed with a set of statistical means, via the Internet to collect data, followed by the analysis of correlations between specific variables. By applying the Pearson chi-square test, 355 questionnaires were distributed, and only 100 were retrieved. The results of the study have showed that there is an impact of green economy practices in achieving competitive advantage, as well as an impact of total quality management practices in achieving competitive advantage in the Romanian operating companies under study. There were no statistically significant differences in the averages of the impact of green economy practices on achieving the competitive advantage. There is a relationship between the use of green economy standards and the subsequent perception of their effectiveness.